PELAKSANAAN FULL DAY SCHOOL DI SDIT NURUL IMAN PALEMBANG - Ratna Dewi; Zuhdiyah Zuhdiyah; Ahmad Syarifuddin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
This study discusses the implementation of the full day school at sdit nurul iman Palembang. The aim of this research is to describe and analyze the implementation of the full day school at sdit nurul iman Palembang to find the implementation of the full day school. This research was motivated bye the lack of rest time for students and family gatherings. This study aims to determine the implementation of full day school and what factors hinder and support its implementation at sdit nurul iman Palembang. The formulation of the problems studied in this study were: (1) How is the implementation of full day school at sdit nurul iman Palembang? (2) What are the factors that hinder and support the implementation of full day school at sdit nurul iman Palembang? This type of reseach is descriptive qualitative. Research informants were the principal, vice principal, teachers, students, parents of students. The data collection techniques in this study used observation, interviews, documentation and triangulation. Based on the results obtained from the field, the implementation of full day school at sdit nurul iman Palembang has been implemented from early 2018 until now and the teaching and learning process is carried out for eight hours every day. The supporting and inhibiting factors faced are the location, school facilities, and activitie.